2023
DOI: 10.1177/23197145221147991
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Impact of Social Media Marketing on Intention to Follow Advice: The Mediating Role of Active Participation and Benevolence Trust

Abstract: The concept of social media marketing (SMM) extends beyond general marketing. SMM has significantly impacted the creation and development of marketing concepts. Drawing on the stimulus (S)–organism (O)–response (R) model, this research aimed to explore benevolence trust, active participation and intention to follow advice (IFA) as three consequences of SMM activities (SMMAs). It also aimed to investigate benevolence trust and active participation as a mediator between SMMAs and IFA with regard to a restaurant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 87 publications
0
4
0
Order By: Relevance
“…, 2011), and e-word-of-mouth (Ge and Gretzel, 2017). However, this intention is important because it could be regarded as an intermediate link between elements in social media marketing and various other travel behaviors, such as purchase, revisit, and brand loyalty (Ibrahim et al. , 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, 2011), and e-word-of-mouth (Ge and Gretzel, 2017). However, this intention is important because it could be regarded as an intermediate link between elements in social media marketing and various other travel behaviors, such as purchase, revisit, and brand loyalty (Ibrahim et al. , 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been found that consumers are more likely to rely on informal sources (such as posts from bloggers) than formal advertisements when making travel decisions (Bansal and Voyer, 2000;Casal o et al, 2011), to what extent they intend to follow the posts has only been explained by exploring a few antecedents in previous studies, such as trustworthiness (Yuan et al, 2022), perceived usefulness of TRPs (Casal o et al, 2011), and e-word-of-mouth (Ge and Gretzel, 2017). However, this intention is important because it could be regarded as an intermediate link between elements in social media marketing and various other travel behaviors, such as purchase, revisit, and brand loyalty (Ibrahim et al, 2023). Therefore, this study advances knowledge of this intention and helps to develop a more comprehensive understanding of how social media contributes to influencing travel behavior.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Trust in social media platforms like Facebook (Meta) is built upon consumer experiences within interactive communities, involving credibility, care, empathy, and consumers' previous interactions with the brand (Vingirayi, 2021). Trust in social media plays a mediating role between social media marketing and purchase intentions (Ibrahim et al, 2023). Moreover, interpersonal trust between users within online communities contributes to brand trust and loyalty (Anastasiei & Chiosa, 2018).…”
Section: Trustmentioning
confidence: 99%
“…For example, collectivist consumers considered friends' influence essential in choosing a favoured brand. In their work, Ibrahim et al (2023) provided evidence that trust in social media mediates between social media marketing and purchase intentions. Anastasiei & Chiosa (2018) proved that interpersonal trust between users within online communities contributes to brand trust and loyalty.…”
Section: Hypothesis Development and Model Formulationmentioning
confidence: 99%